2011
DOI: 10.1073/pnas.1100905108
|View full text |Cite
|
Sign up to set email alerts
|

Protein-specific manipulation of ejaculate composition in response to female mating status in Drosophila melanogaster

Abstract: Female promiscuity can generate postcopulatory competition among males, but it also provides the opportunity for exploitation of rival male ejaculates. For example, in many insect species, male seminal fluid proteins (Sfps) transferred in a female's first mating stimulate increased fecundity and decreased receptivity to remating. Subsequent mates of females could potentially take advantage of the effects of the first male's Sfps and strategically reduce investment in their own ejaculate. We compared postmating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
174
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(192 citation statements)
references
References 52 publications
12
174
6
Order By: Relevance
“…What is even more remarkable is that males appear able to tailor their seminal fluid composition to a particular mating event. Thus, when mating with a virgin female, males will transfer relatively more ovulin than when mating with a previously mated female, presumably because oviposition has already been induced by the female's previous mating partner (Sirot et al 2011). Such strategic adjustments in fecundity enhancing sfps are consistent with the predictions arising from game theoretic modeling of male ejaculate expenditure (Cameron et al 2007, Alonzo & Pizzari 2010.…”
Section: Strategic Adjustments In Seminal Fluid Compositionsupporting
confidence: 75%
“…What is even more remarkable is that males appear able to tailor their seminal fluid composition to a particular mating event. Thus, when mating with a virgin female, males will transfer relatively more ovulin than when mating with a previously mated female, presumably because oviposition has already been induced by the female's previous mating partner (Sirot et al 2011). Such strategic adjustments in fecundity enhancing sfps are consistent with the predictions arising from game theoretic modeling of male ejaculate expenditure (Cameron et al 2007, Alonzo & Pizzari 2010.…”
Section: Strategic Adjustments In Seminal Fluid Compositionsupporting
confidence: 75%
“…Accordingly, in Mediterranean flies, Ceratitis capitata, costs of male courtship were higher than reproduction-induced costs because of sperm production or mating (Papadopoulos et al, 2010). On the other hand, data from Drosophila and crickets point to their ability to modulate the composition of the ejaculate (Sirot et al, 2011;Dowling and Simmons, 2012), and potentially alter the allocation of reproductive costs. Nevertheless, observations of gamete production costs would need to be reconciled with data from worms indicating that removal of the somatic gonad compensates for removal of the germline (Kenyon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These costs can themselves be modulated with age. For instance, female attributes and male age have been implicated in the modulation of sperm production costs (Sirot et al, 2011;Dowling and Simmons, 2012). Nevertheless, naturally occurring genetic variation in males and in females might limit the generality of studies that address molecular mechanisms of reproduction and longevity within a single genotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By manipulating these female traits, males increase their fertilization success. Furthermore, it has been shown that male D. melanogaster strategically adjust allocation of seminal peptides in accordance with female mating status and the perceived risk of sperm competition (Wigby et al 2009;Fedorka et al 2011;Sirot et al 2011) as predicted by theory (Hodgson and Hosken 2006). However, male manipulation comes at a cost to females, as seminal fluid proteins reduce female longevity (Chapman et al 1995) and alter egg production schedules to reduce female lifetime reproductive success (Wigby and Chapman 2005).…”
Section: Nonsperm Ejaculate Substancesmentioning
confidence: 99%